Human Rights in Asia - Davis, Thomas W. D.; Galligan, Brian 1945-. (Cheltenham, U.K. Edward Elgar, 2011)
"This book presents the work of a dozen scholars from Asia and Australasia and draws upon their knowledge of particular countries or aspects of the politics of rights that help in understanding rights in Asia. Most of the contributors participated in an international symposium held at the University of Melbourne in late 2009, with several who could not attend also contributing papers."-- P. xiii.
1. Human rights in Asia : institutions, norms and politics -- 2. Muslim debates on human rights and freedom of religion -- 3. International networks and human rights in Indonesia -- 4. Human rights discourse in post-Marcos Philippines -- 5. Political accountability and human rights in Singapore -- 6. Contesting human rights in Malaysia -- 7. Ambivalent about human rights : Thai democracy -- 8. The challenge for human rights in Cambodia -- 9. Human rights coalitions in Myanmar -- 10. The politics of human rights in India -- 11. China's human rights in 'the Asian century' -- 12. Human rights in Asia : comparative reflections.
Keywords: Human rights -- Asia; Civil rights -- Asia